Perkembangan Kognitif pada Peserta Didik SMP (Sekolah Menengah Pertama) Menurut Jean Piaget - Annisa Mauliya (Program Studi Pendidikan IPA FKIP Universitas Jember, 2019)
The cognitive word comes from the word cognition which has the reliability of the word to know (know). This article aims to find out how the basic concepts of cognitive development in junior high school children (junior high school) according to Jean Piaget. The type of research used is library research. This study focuses on cognitive concepts that occur in children according to Jean Piaget. The implication of Jean Piaget's theory in the process is to help educators to understand the cognitive processes and activities of the participants to help determine the cognitive level of students and choose learning strategies that are in line with the developmental failures of the students.